Taxane and epothilone‐induced peripheral neurotoxicity: From pathogenesis to treatment. (24th October 2019) - Tamburin, Stefano; Park, Susanna B.; Alberti, Paola; Demichelis, Chiara; Schenone, Angelo; Argyriou, Andreas A.
Abstract: Taxane‐induced peripheral neurotoxicity (TIPN) is the most common non‐hematological side effect of taxane‐based chemotherapy, and may result in dose reductions and discontinuations, having as such a detrimental effect on patients' overall survival. Epothilones share similar mechanism of action with taxanes. The typical TIPN clinical presentation is mainly comprised of numbness and paresthesia, in a stocking‐and‐glove distribution and may progress more proximally over time, with paclitaxel being more neurotoxic than docetaxel. Motor and autonomic involvement is less common, whereas an acute taxane‐induced acute pain syndrome is frequent. Patient reported outcomes questionnaires, clinical evaluation, and instrumental tools offer complementary information in TIPN. Its electrodiagnostic features include reduced/abolished sensory action potentials, and less prominent motor involvement, in keeping with a length‐dependent, axonal dying back predominately sensory neuropathy. TIPN is dose‐dependent and may be reversible within months after the end of chemotherapy. The single and cumulative delivered dose of taxanes is considered the main risk factor of TIPN development. Apart from the cumulative dose, other risk factors for TIPN include demographic, clinical, and pharmacogenetic features with several single‐nucleotide polymorphisms potentially linked with increased susceptibility of TIPN. There are currently no neuroprotective strategies to reduce the risk of TIPN, and symptomatic treatments are very limited. This review critically examines the pathogenesis, incidence, risk factors (both clinical and pharmacogenetic), clinical phenotype and management of TIPN.